2003
DOI: 10.1016/s0022-1694(03)00155-0
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the timing of high river flows in New England over the 20th Century

Abstract: The annual timing of river flows is a good indicator of climate-related changes, or lack of changes, for rivers with long-term data that drain unregulated basins with stable land use. Changes in the timing of annual winter/spring (January 1 to May 31) and fall (October 1 to December 31) center of volume dates were analyzed for 27 rural, unregulated river gaging stations in New England, USA with an average of 68 years of record. The center of volume date is the date by which half of the total volume of water fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
173
1
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 223 publications
(194 citation statements)
references
References 27 publications
19
173
1
1
Order By: Relevance
“…Although the intent of the authors was to utilize the relatively similar climate in northern Maine as a point of comparison to southern Maine, Hodgkins et al (2003) found that the timing of peak streamflows in northern Maine over a similar study period changed significantly, while those in southern and coastal Maine, and much of southern New England did not. Peak streamflows, measured as winter/spring centre of volume, were found to occur earlier in northern Maine and these changes were correlated with warmer temperatures and earlier snowmelt.…”
Section: Discussionmentioning
confidence: 99%
“…Although the intent of the authors was to utilize the relatively similar climate in northern Maine as a point of comparison to southern Maine, Hodgkins et al (2003) found that the timing of peak streamflows in northern Maine over a similar study period changed significantly, while those in southern and coastal Maine, and much of southern New England did not. Peak streamflows, measured as winter/spring centre of volume, were found to occur earlier in northern Maine and these changes were correlated with warmer temperatures and earlier snowmelt.…”
Section: Discussionmentioning
confidence: 99%
“…Higher temperatures mean that a greater proportion of the winter precipitation falls as rain rather than snow, and the snowmelt season begins earlier. Snowmelt in parts of New England shifted forward by 1 to 2 weeks between 1936 and 2000 (Hodgkins et al, 2003), although this has had little discernible effect on summer flows (Hodgkins et al, 2005). [WGII 1.3.2]…”
Section: Runoff and River Dischargementioning
confidence: 99%
“…Despite this broad attention to annual streamflow and its connections to global climate processes and precursors, there has been relatively little attention paid to the intra-annual timing of streamflow, emphasizing the need for analysis of seasonal streamflow patterns to further improve understanding of large-scale hydrology and atmospheric behaviors in the main (flood) streamflow season globally (Dettinger and Diaz, 2000). Moreover, better assessment of streamflow timing and seasonality is important for addressing frequency and trend analyses, flood protection and preparedness, climate-related changes, and other hydrological applications that possess important sub-annual characteristics (Burn and Arnell, 1993;Burn and Hag Elnur, 2002;Cunderlik and Ouarda, 2009;Hodgkins et al, 2003). This motivates further investigation of intra-annual temporal streamflow patterns globally.…”
Section: Introductionmentioning
confidence: 99%